Effectiveness of Inforia Interactive Infographics in Enhancing Fourth-Grade Students' Understanding of Archipelago Kingdoms in Social Studies - Setiowati, Aliya Putri; Ali, Enjang Yusup; Karlina, Dety Amelia (Papanda Publisher, 2025)
Education has undergone changes due to digital technology, especially in terms of interactive media that improve student understanding. This study examines the extent to which fourth-grade students understand the Kingdoms in the Archipelago in history lessons using INFORIA (Interactive Infographics of Archipelago History). Sixty-two students were deliberately selected to be divided into an experimental group and a control group in this study, which was conducted at an elementary school in Bandung Regency. P retests, posttests, and student response questionnaires were used to collect data in a quasi-experimental design (Non-Equivalent Control Group Design). With an average pretest score of 44, a posttest score of 80.10, and an N-Gain of 65.39% (moderately effective), the results show that the performance of the experimental group improved significantly. The average pretest score was 40, the average posttest score was 67.16, and the N-Gain for the control group was 44.84% (ineffective). The difference was significant between the groups, as confirmed by an independent sample t-test (p = 0.000 < 0.05). Students also expressed positive opinions about the media in their responses. These results show that INFORIA is a useful and enjoyable tool for improving historical understanding in social studies lessons at the elementary school level.